2015
DOI: 10.1038/srep09055
|View full text |Cite
|
Sign up to set email alerts
|

Superior cycle performance and high reversible capacity of SnO2/graphene composite as an anode material for lithium-ion batteries

Abstract: SnO2/graphene composite with superior cycle performance and high reversible capacity was prepared by a one-step microwave-hydrothermal method using a microwave reaction system. The SnO2/graphene composite was characterized by X-ray diffraction, thermogravimetric analysis, Fourier-transform infrared spectroscopy, Raman spectroscopy, scanning electron microscope, X-ray photoelectron spectroscopy, transmission electron microscopy and high resolution transmission electron microscopy. The size of SnO2 grains deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(58 citation statements)
references
References 56 publications
4
54
0
Order By: Relevance
“…With the development of new electrode materials and technology innovations, LIBs which have high charge-discharge rate and specific capacity, have shown great advantages in the electronic field1234. It has been reported that several kinds of nanostructured, transition-metal oxides5 such as SnO 2 nano-particles can improve the performance of rechargeable LIBs6.…”
mentioning
confidence: 99%
“…With the development of new electrode materials and technology innovations, LIBs which have high charge-discharge rate and specific capacity, have shown great advantages in the electronic field1234. It has been reported that several kinds of nanostructured, transition-metal oxides5 such as SnO 2 nano-particles can improve the performance of rechargeable LIBs6.…”
mentioning
confidence: 99%
“…Both electrodes show the distinct plateaus at around 1 V and 0.6 V vs. Li/Li + in the discharge procedure, ascribing to the electrolyte decomposition and the combination of SnO 2 reduction to Sn metal and the formation of the SEI film [3]. For charge step, we found the plateaus at 0.6 V and 1.3 V vs. Li/Li + for both electrodes, corresponding to the de-alloying reaction from Li x Sn and partially reversible reaction from Sn to SnO 2 [31].…”
Section: Resultsmentioning
confidence: 87%
“…The presence of G peak demonstrates E 2g mode of graphite, which is related to the vibration of sp 2 bonded carbon atoms in a 2-dimensional hexagonal lattice. Meanwhile, the presence of D peak is an indication of defects associated with vacancies, grain boundaries, and amorphous carbon species [18]. Moreover, the presence of 2D peak is the evidence of bi-layer graphene structure and good indication of c axis ordering.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…At rst, speci c capacity initially increases up to 1.1 times during the rst three cycles that can be attributed to the boosting of its porous network structure. During Li insertion and extraction process, in the initial cycles, the TiN clusters pulverize into small particles due to electrochemical milling e ects that lead to more porous nanostructures with more edges, which are able to provide more activated sites for Li storage and also facilitate the penetration of the electrolytes [18,36]. Establishing di usive condition because of SEI formation leads to a capacity retention (C15/C3) of 95%.…”
Section: Electrochemical Performancementioning
confidence: 99%